Association of anthropometric status and residential locality factors with cognitive scores of 4–6-year-old children in Kwazulu-Natal, South Africa. Issue 4 (1st October 2020) - Ajayi, OR; Matthews, G; Taylor, M; Kvalsvig, JD; Davidson, LL; Kauchali, S; Mellins, C
Abstract : Background: The Asenze study has the long-term goal of promoting better physical, cognitive and psychosocial functioning of children in a rural area in KwaZulu-Natal, 50 km from Durban, with a view to planning interventions to promote growth and development for very young children. The specific objective in this paper was to provide information for the Child Health and Development project of the Valley Trust to assist with intervention planning. The broader goal was to assess developmental delays in communities ravaged by the HIV epidemic. The Asenze study was designed in two phases from 2008 and 2012. The current paper reports on 1 581 4–6-year-old children in the baseline phase (2008–2010) in the five adjacent tribal areas in the study area. Method: The participants included all the 4–6-year-olds whose parents had consented to inclusion in the project and their caregivers. Data were derived from a brief questionnaire administered in the homes of participants, and subsequently from medical and psychological assessments of the children and their caregivers at the Asenze clinic. The association between child factors and other factors (geographic area, socioeconomic status (SES), parental level of education, the child's preschool education) on the one hand, and the child's cognitive performance (as measured by the Grover Counter and subtests of the KABC-11) were analysed. Linear regression models were employed to determine which predictor variables of interest in a model were associated with the children's cognitive scores as the dependent variables. Results: Based on the data, the principal factors associated with children's cognitive outcomes were height-for-age z-score (HAZ), preschool education and the area of residence. Generally children who had low cognitive scores were more often stunted (as defined by the WHO anthropometric tables), had not had preschool education, and came from areas less favourable in terms of local infrastructure and access to employment opportunities and arable land. Conclusion: The finding from this cross-sectional analysis of baseline data showed that in addition to height for age and preschool education, which are commonly thought to impact on cognition, the local authority area where the children lived was associated with their scores on cognitive tests. This has implications for intervention planning. The functioning of local government in promoting the type of community development that will protect the rights of children should be taken into account.